Entrepreneurial Institutional Environment and Entrepreneurial Orientation: The Mediating Role of Entrepreneurial Passion - Zhou, Xue; Zhang, Ling; Su, Xiaoyun (Frontiers in Psychology, 2022)
Entrepreneurial institutional environment is the external factor that entrepreneurial enterprises rely on for survival. Our interest is in how entrepreneurs cultivate entrepreneurial orientation in response to the highly uncertain entrepreneurial situation. Based on the cognitive appraisal theory of emotion, we analysed the impact of the entrepreneurial institutional environment on entrepreneurial orientation through entrepreneurial passion. This study applied stepwise regression analyses to test the hypotheses on a sample of 197 entrepreneurs from the co-creation space in China. The output of the study showed that the entrepreneurial institutional environment had a positive effect on entrepreneurial orientation, and entrepreneurial passion played a mediating role between the entrepreneurial institutional environment and entrepreneurial orientation.